Multiwavelength hybrid fiber raman/parametric linear oscillator - Mahdi, Mohd Adzir; Tamchek, Nizam; Abu Bakar, Muhammad Hafiz; Yeo, Kwok Shien; Mahamd Adikan, Faisal Rafiq (Institute of Electrical and Electronics Engineers, 2015)
We demonstrate a linear cavity wideband multiwavelength fiber-based optical parametric oscillator consisting of four fiber Bragg gratings (FBGs). The FBGs center wavelengths are chosen such that they are 3.2 THz (26 nm) and 14.3 THz (115 nm) away from the parametric pump wavelength, with each located in the dominant region of parametric and Raman gain, respectively. Investigation shows that interplay between the lasing processes from the parametric and Raman gain region can be carefully adjusted to produce multiwavelength lasers spanning from 1436 to 1704 nm, with optical signal-to-noise ratio ranging from 14.3 to 54.0 dB.